Molecular Networking and Bioassay-Guided Preparation and Separation of Active Extract and Constituents from Vicia tenuifolia Roth - Duc Dat Le; Soojung Yu; Thinhulinh Dang; Mina Lee (MDPI AG, 2023)
Molecular networking drove the selection of material from V. tenuifolia organs that targeted active flavonoid glycosides. To optimize the extraction process, the flowers of V. tenuifolia were used to produce an anti-inflammatory extract. The effects of variables-organic solvent ratio; extraction time; and temperature-were investigated by the response of anti-inflammatory activity. Bioactivities-guided experiments helped identify fractions with high total phenolic and flavonoid content as well as antioxidant potential. Furthermore, one new compound (1), 19 first isolated together, and two known compounds were obtained and identified from the active fraction of this plant. Among them, compounds (15 and 22) were first reported for nuclear magnetic resonance (NMR) data from this study. All the isolates were evaluated for their anti-inflammatory capacity throughout, modulating nitric oxide (NO), interleukin (IL)-1β, and IL-8 production. Active compounds were further investigated for their regulation and binding affinity to the inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) proteins by Western blot and in silico approaches, respectively. The findings of this study suggested that the developed extract method, active fraction, and pure components should be further investigated as promising candidates for treating inflammation and oxidation.